EFFECTS OF MANAGERS’ INDIVIDUAL INNOVATIVE BEHAVIOR TENDENCIES AND BUSINESS INNOVATION ON NON-FINANCIAL BUSINESS PERFORMANCE - Feridun Duman; Sevcan Vardar (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Innovationglobally gains its speed day by day and is now seen as the key to progress anddevelopment. In recent years, innovation in firms has showed a necessity of individual innovativeness.This necessity of innovative individuals is seen asa significant responsibility of hotelmanagers. Both individual innovative tendencies of managers andbusiness innovation are of importance for the survival of the firms as well ascompetitive rivalry resulting in better performance. Thus, this study aims tofind out the effects of managers’ innovative behaviour tendencies and businessinnovation on the non-financial business performance. A questionnaire survey wasconducted on 22 five-star city hotels located in Ankara, the capital of Turkey.Factor, regression and correlation analyses were used to test the studyhypotheses. The findings showed that the "resistance to change"dimension of managers’ individual innovative behaviour tendencies has anegative effect on the non-financial business performance while the dimensionsof “leadership in ideas”, “openness to experience” and risk-taking” did notproduce any effect on the non-financial business performance. The study alsofound that the hotels follow “customer focused” innovation, which shows thecustomers are at the centre of all the hotel operations. The study furthershowed that there is a positive and significant relationship between managers’individual innovative behaviour tendencies and business innovation.